Best Practices in Teaching Approaches for Teaching English at Elementary Schools: The Experiences of Former Students of PPG Prajabatan - Firdaus, Ahmad Royhan; Vianty, Machdalena (Journal of English Language and Education, 2025)
This study investigates best practices in teaching English at elementary schools as implemented by alumni of the PPG Prajabatan Program from Sriwijaya University who currently teach in Palembang. Using a qualitative research design, data were collected through semi-structured written interviews with three PPG Prajabatan 2022 alumni who have one to three years of teaching experience at the elementary level. The study focused on identifying concrete teaching practices that support student engagement and language development in early EFL classrooms. Data were analyzed through thematic analysis following Braun and Clarke’s procedures, including familiarization with the data, initial coding, theme development, and interpretation. The findings revealed three major best practices: differentiated instruction tailored to students’ readiness and learning styles, communicative and game-based learning to promote active language use, and flexible integration of multiple teaching approaches adjusted to classroom needs and lesson objectives. Rather than applying a single method, participants combined various strategies to create meaningful and enjoyable learning experiences. These findings contribute to a deeper understanding of how professionally trained teachers translate pedagogical knowledge into classroom practice. Practically, the study offers insights for teacher education programs, particularly PPG Prajabatan, to strengthen reflective practice, instructional flexibility, and creativity in preparing future English teachers for elementary school contexts.